HELICOBACTER PYLORI INFECTION: AS A RISK FACTOR FOR ANEMIA, A PHYSIOLOGICAL PERSPECTIVE FROM SHAHEED BENAZIRABAD - Ghulam Muhammad Phull; Altaf Hussain Memon; Bhojo Mal Tanwani; Altaf Khan Pathan; Masood Nabi Noor Dhahri; Sikander Ali Bhand (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Helicobacter pylori infection is a very common entity these days in children and adults irrespective of the gender and religion and its impact on health is quite disturbing. The current study was planned and executed to evaluate the impact of H. Pylori infection on the hemoglobin levels and RBCs morphology and indexes. Methods: This case control study, carried out in the outpatient department of the People Medical College Hospital, Nawabshah, Sindh, Pakistan over 06 months. There were 384 study participants, 192 helicobacter pylori +ve patients and 192 healthy individuals as controls. Patients were randomly selected with an age ranging10 years to 60 years. Blood samples taken under aseptic measures were analyzed for hematological evaluations. Results: The mean age was 37.21+5.11 years in H-pylori infected individuals (Group-A) while it was 33.11+4.51 years in controls(Group-B). There were 168 males and 216 females among the study participants. A significant difference was observed in RBC count among the two groups, 3.1±1.0 x 106million/mm3 and 4.8±1.9 x 106million/mm3 in Group-A and Group-B respectively (p-0.03). Similarly significant difference was observed in MCV for the two study groups which was 71.04±7.1fl and 84.13±6.8 fl for Group-A and Group-B respectively (0.001). Significant statistical difference was found in MCH and RDW among the two groups. Conclusion: H. Pylori infection significantly affects RBCs count and morphology which may lead to microcytic and hypochromic anemia in patients suffering from this infection.